A Repeated Lie Becomes a Truth? The Effect of Intentional Control and Training on Deception - Hu, Xiaoqing; Chen, Hao; Fu, Genyue (Frontiers in Psychology, 2012)
Deception has been demonstrated as a task that involves execution control such as conflict monitoring and response inhibition. In the present study, we investigated whether or not the controlled processes associated with deception could be trained to be more efficient. Forty-eight participants finished a reaction times (RTs)-based differentiation of deception paradigm (DDP) task using self- and other-referential information on two occasions. After the first baseline DDP task, participants were randomly assigned to one of three groups: a control group in which participants finished the same task for a second time; an instruction group in which participants were instructed to speed up their deceptive responses in the second DDP; a training group in which participants received training in speeding up their deceptive responses, and then proceeded to the second DDP. Results showed that instruction alone significantly reduced the RTs associated with participants’ deceptive responses. However, the differences between deceptive and truthful responses were erased only in the training group. The result suggests that the performance associated with deception is malleable and could be voluntarily controlled with intention or training.